Lipreading in the prelingually deaf: what makes a skilled speechreader? - Rodríguez Ortiz, Isabel De Los Reyes (The Spanish Journal of Psychology, 2008)
Lipreading proficiency was investigated in a group of hearing-impaired people, all of them knowing Spanish Sign Language (SSL). The aim of this study was to establish the relationships between lipreading and some other variables (gender, intelligence, audiological variables, participants’ education, parents’ education, communication practices, intelligibility, use of SSL). The 32 participants were between 14 and 47 years of age. They all had sensorineural hearing losses (from severe to profound). The lipreading procedures comprised identification of words in isolation. The words selected for presentation in isolation were spoken by the same talker. Identification of words required participants to select their responses from set of four pictures appropriately labelled. Lipreading was significantly correlated with intelligence and intelligibility. Multiple regression analyses were used to obtain a prediction equation for the lipreading measures. As a result of this procedure, it is concluded that proficient deaf lipreaders are more intelligent and their oral speech was more comprehensible for others.